Sistem Pendukung Keputusan Penerimaan Pegawai Baru Pada Pabrik Penggilingan Padi Dengan Metode Weighted Product - Rina Wati; Agus Sulistia Winanda; Helisia Margahana; Erma Dwiyani (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Recruitment is a process of search and withdrawal of workers who have the potential to fill vacancies, qualified workforce is very influential on the performance of the company's progress. In the decision-making process of production employee acceptance is still influenced by subjectivity factor and the company often has difficulty in choosing the employee, because the number of prospective employees who apply for while to be accepted become very limited employee. This study uses the method of weighted product because the method of weighted product is one method of completion of multi criteria where in the recruitment of many criteria to be considered.